The extent of adopting a number of green processing chain management activities in industrial companies An analytical study behind a sample of workers in Kirkuk Cement Factory - علي سوزان عبد الغني; محسن اياد فاضل (Journal of Economics and Administrative Sciences, 2019)
The research is based on the basic idea that companies today are moving towards a new trend towards protecting the environment coupled with the increasing wareness of the pollution damage caused by these companies due to their operations and activities in the environment. The two main reasons that led the researchers to choose this subject is the need to adapt the companies themselves in response to successive developments, The great development was that companies moved from the sole economic responsibility of the business to social responsibility by emphasizing socially responsible profit. The problem of research is the knowledge of the availability of the dimensions of the green processing series in Kirkuk Cement Factory The research stems from the fact that it dealt with an industry sector that has a direct impact on the environment of the society through which it is affected negatively or positively. The aim of the research is to find out the availability of the dimensions of the green processing series in the research lab. The research sample consisted of 30 employees who have know- And the hypothesis of research was tested using statistical analysis (T) and variance And the percentages and frequencies to distinguish the dimensions of research according to availability in the laboratory in question, and the research concluded a set of conclusions, the most important: the interest of the laboratory in the activities of the management of the green processing chain, as these activities are integrated between them and the researchers made a set of recommendations that are consistent with the conclusions The most important of these is the need for increased attention from the laboratory to the dimension of green procurement and processing through the efficient treatment of waste